2015
DOI: 10.1007/s00709-015-0850-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of superoxide dismutase (SOD) isozymes by organ development and high long-term salinity in the halophyte Cakile maritima

Abstract: Superoxide dismutase (SOD) activity catalyzes the disproportionation of superoxide radicals into hydrogen peroxide and oxygen. This enzyme is considered to be a first line of defense for controlling the production of reactive oxygen species (ROS). In this study, the number and type of SOD isozymes were identified in the principal organs (roots, stems, leaves, flowers, and seeds) of Cakile maritima. We also analyzed the way in which the activity of these SOD isozymes is modulated during development and under hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 69 publications
2
36
0
Order By: Relevance
“…The number of SOD unigenes are different in plants reported. For example, there are 7 SODS in Arabidopsis [33], 10 SODs in Cakile maritima [34], and 4 SODs in pepper [35]. A total of 29 and 18 SOD genes have been identified in Brassica juncea and Brassica rapa, respectively [36].…”
Section: Discussionmentioning
confidence: 99%
“…The number of SOD unigenes are different in plants reported. For example, there are 7 SODS in Arabidopsis [33], 10 SODs in Cakile maritima [34], and 4 SODs in pepper [35]. A total of 29 and 18 SOD genes have been identified in Brassica juncea and Brassica rapa, respectively [36].…”
Section: Discussionmentioning
confidence: 99%
“…Most plant tissues contain at least one Fe-SOD, although in this work, we were not able to detect any Fe-SOD activity in pomegranate. So, in order to confirm the absence of this isozyme, western blotting assays using an antibody against Fe-SOD from pepper (Capsicum annuum) fruits [54], (also characterized in other plant species like Olea europaea [53] and Cakile maritima [55]), were carried out. Interestingly, one cross-reacting band of about 23 kDa was detected in all seeds and juices from F-GR and E-A samples.…”
Section: Resultsmentioning
confidence: 99%
“…Both pomegranate populations share the same isozyme profile but the activity of some of them was much higher in E-A seeds than in F-GR. In previous works, it was found that SOD activity was used as index of the cultivar and ripening stage, and it was described that this enzyme also participated in the response against diverse unfavorable conditions [14][15][16][17][18][19]55]. Recently, by iTRAQ analysis, the presence of a SOD from the Fe,Mn family has been reported [32], but no CuZn-SODs have been described so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the characterization of plants has been conducted not only based on morphological characters but also the isozyme banding pattern as reported by Premoli (2003) and Zolfghari et al (2010). The use of plant isozyme in the characterization of plants have been conducted widely (Rejon et al 2012;Houmani et al 2016;Hartanti et al 2017).…”
Section: Introductionmentioning
confidence: 99%